2008
DOI: 10.1177/1049732308328052
|View full text |Cite
|
Sign up to set email alerts
|

The Body Projects of University Students with Type 1 Diabetes

Abstract: Young adults with type 1 diabetes are a "forgotten group." Their perspectives are rarely addressed by research studies, meaning that we know little about the reasons why they engage (or not) in diabetes self-care practices. The limited work that has investigated these young people's perspectives suggests that they experience a tension between being healthy and being normal. In this article, I examine this tension from the viewpoints of a particular group of young adults with diabetes: university students. I ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 38 publications
0
57
0
Order By: Relevance
“…These included: inclement weather and ensuing unpredictable fluctuations in their child's activity levels; other people's ignorance and inappropriate feeding practices; and physiological and social changes accompanying childhood development which, as Kushion et al [17] have observed, can require a child's insulin requirements to change as frequently as every 2 weeks. In addition, and in keeping with findings from studies with adolescents and adults with diabetes [18][19][20], parents described needing to balance strict diabetes management against enabling their child to lead a 'normal' life. For all these reasons, parents discussed how keeping their child's blood glucose levels within target ranges was often an unrealistic and unrealisable task and, hence, how they felt diabetes professionals were unduly judgemental when good control was not achieved.…”
Section: Discussionmentioning
confidence: 84%
“…These included: inclement weather and ensuing unpredictable fluctuations in their child's activity levels; other people's ignorance and inappropriate feeding practices; and physiological and social changes accompanying childhood development which, as Kushion et al [17] have observed, can require a child's insulin requirements to change as frequently as every 2 weeks. In addition, and in keeping with findings from studies with adolescents and adults with diabetes [18][19][20], parents described needing to balance strict diabetes management against enabling their child to lead a 'normal' life. For all these reasons, parents discussed how keeping their child's blood glucose levels within target ranges was often an unrealistic and unrealisable task and, hence, how they felt diabetes professionals were unduly judgemental when good control was not achieved.…”
Section: Discussionmentioning
confidence: 84%
“…Certain elements of university life have been identified in the research literature as barriers or challenges to achieving appropriate diabetes self-management in this population. These include the following: (1) social issues, such as peer pressure, alcohol consumption (6,10), smoking, drug abuse (4,6,17e20), dietary constraints (4,5,15) and eating disorders (6); (2) academic barriers, such as irregular schedules and routines, lack of time and financial issues (4,5,19); and (3) emotional and psychological barriers, such as stress (5), insufficient or lack of social support (5,21), loss of parental involvement (4,17), denial and rebellion toward diabetes self-management (5), and emotions of anger, frustration and sadness as a result of feeling isolated from peers (22).…”
Section: Introductionmentioning
confidence: 99%
“…Both also displayed concerns about the potential disruption to romantic relationships. Whilst concerns about the effect of illness on these relationships could equally be felt at any age, the search for a long‐term partner and pressure to conform to certain body image types has been found to be characteristic of young adulthood (Balfe , Raymore et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst concerns about the effect of illness on these relationships could equally be felt at any age, the search for a long-term partner and pressure to conform to certain body image types has been found to be characteristic of young adulthood (Balfe 2009, Raymore et al 2001. Young adulthood has also been proposed to be a time during which individuals are forming a stable self-identity, and is commonly seen as a period of transition; attending university in particular has been found to bring its own set of pressures, expectations, as well as temptations and desires (Balfe 2009, Saunders 2011). All of this can mean that for many, the biography being disrupted by illness is already potentially in a state of flux and instability, and it can therefore be argued that disruption to a sense of self and life-context that is already somewhat fragile may be all the more devastating.…”
Section: Experiencing Disruption In Young Adulthoodmentioning
confidence: 99%